Effect of the Carbon Source Flow Rate on the Quality of the Growth of Super-Aligned Carbon Nanotube Arrays by the Chemical Vapor Deposition Method - S. Asadi; M. R. Vahdani; R. Mardani (Iranian Journal of Chemical Engineering)
In this study, carbon nanotubes were fully aligned by chemical vapor deposition at atmospheric pressure on a silicon substrate at two carbon source flow rates of 28 and 38 sccm (standard cubic centimeter per minute). Acetylene gas (C2H2) as the carbon source for argon gas (Ar) as the carrier gas for hydrogen gas (H2) for the recovery of the nanoparticle and iron nanoparticles as the catalytic source at 800 °C were used for the growth of the carbon nanotube array. The reaction was carried out in a 48 cm long quartz tube and the gases were injected with specified flow rates. The silicon substrate was coated by the magnetic sputtering method with catalytic iron nanoparticles with a thickness in the range of 3-6 nm. The results of the FESEM analysis showed, as the carbon source flow rate was increased to 38 sccm, the average diameter of the grown carbon nanotubes is increased, and the carbon nanotubes with a diameter of 60-70 nm were most abundant.